Dynamiques rurales et conservation forestière dans le Nord de la Tunisie - Amor Mokhtar Gammar (Revue de Géographie Alpine)
This paper will first examine the causes of the ongoing forest crisis that was inherited from the French protectorate and that is associated with the agricultural and forest policies followed by the Tunisian government. Strict forest regulations have failed to contain increased population pressure on forest lands. This is mainly due to the crisis of traditional agriculture that has been undermined by large and modern production-driven exploitation of large basins, which is promoted by the agricultural policies of the state and supported by a powerful urban framework. Then, this article will show how, in recent decades, the multiplicity of original rural dynamics tends to give new clear-cut characteristics to the rural populations and their territories in the mountain forests. In particular, it focuses on issues like the reshaping of rural communities, diversification of peasants’ income generation activities, and the dynamism of certain peasant economy. These sufficiently advanced changes are lightening the pressure of the population on the forest lands, and they especially modify Man-vegetation relationships, towards the reconciliation between the peasants and the forests. They therefore call for a re-thinking of forest policies to clearly integrate resident peasants into forest management and development.